Velázquez pintando (1998)
Any artist needs a series of materialelements that provide form tohis creative ideas. T he artist' s successdepends greatly on his choice ofthese elements and on his masteryof them. Research mz the metlwdsused and on the deciphering of someof the secret resources of the painterare at present some of the most attractiveand suggestive topics thathistory of art today provides us.